Development of antimicrobial and antioxidative chicken patties using liquid-fermented Ganoderma lucidum and Pleurotus djamor fruiting body biomass - Zahia-Azizan, Nur Asyiqin; Yee, Chong Shin; Ushidee-Radzi, Muhammad Ameer; Ilham, Zul; Abd Rahim, Muhamad Hafiz; Raseetha, Siva; Hamid, Nazimah; Jamaludin, Adi Ainurzaman; Wan-Mohtar, Wan Abd Al Qadr Imad (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Medicinal mushroom production utilising rural cultivation (solid state fermentation) requires approximately six months compared to culinary mushroom production (7 days). Urban cultivation (submerged liquid fermentation) can be used as a sustainable method of producing medicinal mushroom biomass. In this study, chicken patties were fortified with liquid-fermented Ganoderma lucidum flour (GLF) and Pleurotus djamor mushroom biomass flour (PDF) at concentrations of 3%, 6%, and 9%. These were compared to a negative control (0% mushroom flour chicken patty) and a commercial patty. Chicken patties fortified with 3% PDF and 9% GLF recorded the lowest cooking loss, at 5.55% and 10.3%, respectively. Mushroom chicken patties exhibited lower cooking losses and significant changes in colour and texture compared to control samples. Notably, 3% GLF chicken patty achieved the highest overall acceptability score of 6.55 followed by 9% PDF chicken patty (6.08) (p < 0.05). Biomass flour of liquid-fermented Ganoderma lucidum (ENS-GL) and Pleurotus djamor (ENS-PD) were extracted for their endopolysaccharide and analysed for their functional properties. All elemental, FT-IR, and NMR spectroscopy analyses revealed the existence of a comparable beta-glucan polymer structure, linkages, and absorptions when compared to the Laminarin standard. In addition, ENS-GL also proved to possess higher antimicrobial activities and significant antioxidant levels (DPPH-scavenging activity, ferric reduction potential and total phenolic content) compared to ENS-PD. Overall, this study revealed that sustainable liquid-fermented Ganoderma lucidum, a medicinal mushroom, outperformed Pleurotus djamor, a culinary mushroom, as a potential alternative flour for combating hunger in the future.